2007
DOI: 10.1021/ja0631246
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of Boron:  The Role of Defects and Zero Point Motion

Abstract: Its low weight, high melting point, and large degree of hardness make elemental boron a technologically interesting material. The large number of allotropes, mostly containing over a hundred atoms in the unit cell, and their difficult characterization challenge both experimentalists and theoreticians. Even the ground state of this element is still under discussion. For over 30 years, scientists have attempted to determine the relative stability of alpha- and beta-rhombohedral boron. We use density functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

17
159
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(181 citation statements)
references
References 48 publications
17
159
2
3
Order By: Relevance
“…These complex structures make it difficult to interpret and understand the relationships between structure and properties. Indeed, even the ground state structure of boron has been controversial for over 30 years [6,[15][16][17].A number of crystalline structural forms for elemental boron have been discovered over the last two centuries [18][19][20]. However, only three phases correspond to pure boron: α-B 12 [18], β-B 105 [19], and γ-B 28 [20], with most of the others probably stabilized by impurities [21][22][23].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…These complex structures make it difficult to interpret and understand the relationships between structure and properties. Indeed, even the ground state structure of boron has been controversial for over 30 years [6,[15][16][17].A number of crystalline structural forms for elemental boron have been discovered over the last two centuries [18][19][20]. However, only three phases correspond to pure boron: α-B 12 [18], β-B 105 [19], and γ-B 28 [20], with most of the others probably stabilized by impurities [21][22][23].…”
mentioning
confidence: 99%
“…However, the quantum mechanics studies [15,16] predict that the α-B 12 structure is more stable than β-B 105 by 25.3 meV=atom, leading to a long debate of which phase is the ground state structure for elemental boron [6,[15][16][17]24]. Recent quantum mechanics studies have suggested that particular choices for the partial occupation sites in β-B 105 and including zero point motion might lead to an energy for β-B 105 that is more stable than α-B 12 structure at ambient conditions [16,25].Twinned structures have been observed in β-B 105 [26,27] and boron related materials such as B 4 C [28]. Although the growth conditions to form these twinned structures are not clear [27,29], the twinned structure might dramatically change material properties such as charge capacitance [30].…”
mentioning
confidence: 99%
See 3 more Smart Citations